PENGGUNAAN MEDIA UBUR-UBUR PADA MATERI LUAS BANGUN DATAR UNTUK MENUMBUHKAN MOTIVASI BELAJAR SISWA KELAS 5 SEKOLAH DASAR - Fitri Setiyowati; Yulina Ismiyanti; Yunita Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Mathematics learning in elementary schools has a crucial role in building a basic understanding of numeracy concepts for students. Therefore, learning must be designed optimally so that students do not only understand numbers and formulas. This research aims to examine whether jellyfish media in mathematics learning can increase the learning motivation of grade 5 students at Sultan Agung Islamic Elementary School 4, especially in understanding the area of ​​flat shapes. This type of research is in the form of a case study, with a descriptive qualitative approach. Data collection techniques use observation, questionnaires and documentation, then analyzed using data reduction techniques, data presentation and drawing conclusions. And checked using the validity of triangulation technique which consists of source triangulation, theoretical triangulation, technical triangulation and time triangulation. Based on research results, the use of jellyfish media in teaching mathematics on the concept of area of ​​flat shapes has proven to be effective in increasing motivation and understanding of grade 5 students at Sultan Agung Islamic Elementary School 4. This media provides a more interesting and interactive learning experience, so that students are more active in the learning process. Thus, jellyfish media can be an innovative alternative in teaching mathematics in elementary schools. Not only does it help students understand concepts better, this media also creates a fun learning environment and encourages the development of critical thinking skills.